Efeitos no consumo de oxigênio e qualidade de vida do treinamento intervalado de alta intensidade em mulheres durante e após tratamento quimioterápico do câncer de mama: revisão sistemática e metanálise - Fontes, Karina Prado (2020)
Introduction: The survival of breast cancer patients has increased, generating a greater concern for the individual's global well-being. Chemotherapy treatments can cause cardiorespiratory limitations, hampering the daily activities of these patients. Objective: The aim of this study was to conduct a systematic review and meta-analysis of publications of randomized controlled trials in women during and after chemotherapy treatment for breast cancer that investigates the general effect on quality of life and changes in physical fitness resulting from training high intensity interval (HIIT). Methods: The searches were carried out in the PubMed, Cochrane and Scopus databases. Inclusion criteria for this systematic review included participants aged 18 years or older who were diagnosed with breast cancer during and after chemotherapy, physical inactivity in the last six months and who participated in supervised training (HIIT) for at least 6 weeks. The PICO search strategy was adopted: P (patient) = breast cancer treated with chemotherapy; I (intervention) = high intensity interval training (HIIT); C (control) = conventional care or other training modality; O (outcome) = peak VO2 (peak oxygen consumption) and quality of life; T (type of study) = randomized clinical trials. Results: A total of 8 studies with 414 participants were included. Peak VO2 was statistically significant (p <0.00001) with a difference in subtotal mean and 95% CI favoring HITT compared to control and quality of life by EORTC, we observed a significance, but it does not show clinical relevance, since the diamond touches the zero line. Conclusion: This systematic review and meta-analysis showed that HIIT induces positive effects on oxygen consumption and quality of life, however studies are needed for patients with breast cancer in all phases of therapy and aftercare.